Cross-sectional survey on bacterial co-infections in Peste des Petits Ruminants virus-infected small ruminants in Enugu State, Nigeria - Chukwudi, IC; Ogbu, KI; Ugochukwu, IC; Daodu, OB; Duile, PE; Obiekwe, UC; Nwankwo, SE; Animoke, PC; Ikenna-Ezeh, NH; Oyeleye, O; Ogunniran, TM; Momoh-Abdulateef, H (Journal of the Hellenic Veterinary Medical Society, 2024)
Small ruminant productivity in Nigeria has been hampered by the Peste des Petits Ruminants Virus (PPRV) and a subsequent bacterial infection. It is vital to understand the most prevalent bacteria that might exacerbate PPRV disease in order to enhance the prognosis and treatment of PPRV patients. Sheep and goats offered for sale at local markets in Nigeria's Enugu state were examined for typical clinical manifestations of PPR infection and selected for this study. Two hundred and ten ocular, nasal and oral swab samples were collected from 70 sheep and goats. An additional 70 nasal swabs were collected for molecular confirmation by reverse transcriptase polymerase chain reaction, while the remainder were used for bacterial isolation and identification. The detection rate of the PPRV gene was 25.7% (18/70), affecting three sheep (4.3%; 3/70) and 15 goats (21.4%; 15/70). Based on the PPRV-positive animals, 72 bacterial isolates consisting of eight genera and eleven species were obtained. Staphylococcus aureus was the most frequently isolated gram-positive bacterium (31.9%; 23/72), while Escherichia coli was the most frequently isolated gram-negative bacterium (19.44%; 14/72). Staphylococci were the most frequently isolated bacteria from all samples. This study found that small ruminants infected with PPRV were sold in the study area, providing a potential means of spreading the disease to other animals. In addition, it is highlighted that several bacteria, some of which might belong to the normal flora, might complicate and worsen the clinical presentation of PPRV cases.